Development of technology for obtaining juice from persimmon fruit (Diospyros kaki L.) - Mikayilov, Vugar; Omarova, Elza; Kazimova, İlhama and Aliyeva, Jamila and Fatma, Aliyeva and Gasimova, Afet and Nabiyev, Ahad (Eastern-European Journal of Enterprise Technologies, 2024)
Organizing proper and environmentally friendly nutrition is one of the most pressing problems. Widespread persimmon fruits are of great technological importance as raw materials for the production of concentrated juice, used as a natural sweetener. The object of this study is the processes of obtaining juices from persimmon fruits. Quality indicators were studied in juices prepared by preliminary heat treatment and the use of an enzyme preparation. The juice yield from the Khachia variety was 93.9 %, and from the Hiakume variety – 93.8 %. To prepare concentrated juice, persimmon juice was used, prepared by preliminary heat treatment, and using 0.1–0.2 % enzyme preparation. A scheme for preparing concentrated juice has been developed, which is recommended for use as an environmentally friendly sweetener in food production. The concentrate contained 7.25 µg/100 g of iodine. The prepared concentrate is rich in nutritional components necessary for human life, as well as sugars, phenolic compounds with antioxidant and antimicrobial properties, as well as vitamin C. Nutritional components perform a wide range of functions in the optimal functioning of the immune system and play an important role in metabolic processes. The use of persimmon concentrate in the preparation of various food products increases the bioavailability of many minerals. Therefore, to ensure the nutritional value of the finished product and increase long-term quality storage, it is recommended to use concentrated persimmon juice as a sugar substitute